L4: Water Governance in the Limpopo Basin - Love, David; Kileshye Onema, Jean-Marie; Goldin, Jacqui (2011)
The project focuses on access and control of water/land, and the associated management and governance mechanisms. L4 seeks to provide the people and governments of the Limpopo Basin with: 1. A package of ways to better understand and organise access rights to water for multiple uses from farm level to the basin and regional level, 2. A package of ways to organise technologies for different physical and socio-economic contexts so as to improve the management and control of water for multiple uses from one or more water sources, 3. A suite of policy and legal options to support agriculture-based livelihoods in which water plays a vital role, and 4. A set of institutional arrangements that is appropriate for different classes of smallholder farmers including the resource poor, women farmers, and other disadvantaged groups. The issues that have been raised above encompass the full water cycle, which makes it important to consider at the same time management of rainwater (for rainfed agriculture and rainfed pasture, for example) – the green water component – alongside the better management of runoff, groundwater and stored surface water - the blue water component. This has important social and institutional implications – and also policy and legal implications, as southern Africa moves from the management of shared flowing water to the management of rainfall across the shared basins such as the Limpopo (Ncube et al, 2009).